Решите уравнение: а) (x-2)(x+3)=x(2-x) б) х(2х+1)=(2х+1)2

Решите уравнение: а) (x-2)(x+3)=x(2-x) б) х(2х+1)=(2х+1)2
Гость
Ответ(ы) на вопрос:
Гость
а)  (x-2)(x+3)=x(2-x) X(2)+3x-2x-6=2x-X(2)   ----  число "2" после икс пиши сверху 2X(2)+x-2x=6 2X(2)-x=6 x(2x-1)=6 x=6  или   2x-1=6         2x=7         x=3,5   ответ: 6; 3,5   б)  х(2х+1)=(2х+1)(2)      2х(2)+х=4х(2)+1+4х 2х(2)+х-4х(2)-4х=1 -2х(2)-3х=1 х(-2х-3)=1 х=1  или  -2х-3=1                -2х=4                х=-2   ответ: 1;-2
Не нашли ответ?
Ответить на вопрос
Похожие вопросы